2017
DOI: 10.1149/2.0181802jes
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Mechanism of Electrochemical Formation of Magnetite Nanoparticles by In Situ Raman Spectroscopy

Abstract: The formation of magnetite nanoparticles (Fe 3 O 4 -NPs) by electro-oxidation process was studied by in situ and ex situ techniques in chloride electrolytes with and without ethanol. The electrochemical synthesis is characterized by the application of a current disturbance that promotes the oxidation of a low carbon steel electrode in solution to an oxidized state (Fe 2+ ) which is subsequently transformed into magnetite by reactions in solution. The electrochemical synthesis results in a final product of pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 80 publications
3
15
0
Order By: Relevance
“…This species then reacts in the bulk solution with dissolved dihydrogen formed in the cathode to obtain the magnetite (reaction ). However, the anodic reaction involving three electrons and three hydroxide molecules is unlikely to occur in a single step.At the cathode, water reduction (reaction ) occurs, and in the bulk solution Conversely, Lozano et al showed that hydrogen is not a reducing agent of lepidocrocite (γ-FeOOH) (reaction ), which is also in agreement with the work of Montoya et al…”
Section: Results and Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…This species then reacts in the bulk solution with dissolved dihydrogen formed in the cathode to obtain the magnetite (reaction ). However, the anodic reaction involving three electrons and three hydroxide molecules is unlikely to occur in a single step.At the cathode, water reduction (reaction ) occurs, and in the bulk solution Conversely, Lozano et al showed that hydrogen is not a reducing agent of lepidocrocite (γ-FeOOH) (reaction ), which is also in agreement with the work of Montoya et al…”
Section: Results and Discussionsupporting
confidence: 73%
“…Indeed, Lozano et al 12 and Montoya et al 13 devised mechanisms in which only Fe 2+ is generated at the anode, while the other reactions of the mechanism take place in the homogeneous phase.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations